WTO DISPUTE SETTLEMENT MECHANISMS IN THE CONTEXT OF INCREASING ASYMMETRY IN GLOBAL TRADE - Kudyrko , L.P.; Toniuk , Y.V. (The actual problems of regional economy development, 2025)
This article examines current trends in the resolution of interstate trade disputes through the mechanisms of the World Trade Organization, with an emphasis on identifying the key factors influencing their effectiveness. To study this issue, a set of methods was used, in particular: statistical method, comparative analysis, elements of the institutionalist approach. The study reveals that asymmetries in international trade are deepening, while the effectiveness of WTO mechanisms in resolving disputes among member states is declining. As global trade governance instruments weaken, alternative approaches to dispute resolution are increasingly emerging. The rise of economic nationalism among member states as a regulatory norm exacerbates trade conflicts. Countries with limited economic power, often engaging in trade with stronger partners, are particularly dependent on effective protection mechanisms for their interests. Sectoral analysis of trade disputes for 2023–2025 highlights growing tensions in areas such as domestic market protection, environmental regulation, and state support for strategic industries. Disputes have intensified in sectors including electric vehicles, agricultural products, and new tariff regimes, indicating a shift in the focus of trade conflicts and posing new challenges for the WTO dispute settlement system. The theoretical value of the study lies in synthesizing current developments in WTO dispute resolution and assessing how global processes affect this institutional mechanism. The findings contribute to the broader understanding of international trade policy evolution and may serve as a basis for refining theoretical approaches to global trade in the context of widening development asymmetries among WTO members. The study's practical significance stems from its potential to inform improvements in mechanisms for protecting national trade interests. Further research should explore the effectiveness of alternative dispute resolution methods outside the WTO, particularly in the context of asymmetric regional trade agreements and digital trade, which present emerging challenges for global trade governance.